Transposed identity negotiation: A new conceptual framework - McAllester, Kelly (Journal of International Students, 2024)
International students negotiate various intersecting identities while studying abroad. When an international student moves into the new spatial context of their host country, the student’s intersectional identity is perceived with degrees of marginalization or privilege by host country nationals that conflict with the student’s understanding of their identities in their home context. Existing frameworks from various theoretical traditions describe how students experience identity negotiation and construction, yet there is no synthesized conceptualization of how students negotiate identity when intersectional identities are relocated, or transposed, into a new spatial context.